Small bowel metastasis from endometrial cancer presenting as a bowel obstruction: A case report with literature review - Yasuhiko Hamada; Hiroki Yukimoto; Yohei Ikenoyama; Yuhei Umeda; Yasuko Fujiwara; Akina Shigefuku; Hiroto Suzuki; Misaki Nakamura; Noriyuki Horiki; Hayato Nakagawa (DEN Open)
Abstract This report describes a rare case of small bowel metastasis from endometrial cancer, diagnosed six years after initial treatment. A 62‐year‐old woman with a history of grade 2 stage IA endometrial cancer, previously treated with hysterectomy and bilateral salpingo‐oophorectomy, presented with intermittent abdominal pain and nausea. Imaging studies revealed small bowel obstruction and balloon‐assisted enteroscopy identified an annular ulcer with luminal narrowing in the jejunum. Histopathological examination of the biopsy specimen suggested carcinoma; however, its primary origin remained unclear. Subsequent surgical resection confirmed metastatic endometrial adenocarcinoma based on immunohistochemical analysis, which demonstrated positivity for estrogen receptor and paired box gene 8, while CK7, CK20, and CDX2 were negative. Following surgery, the patient experienced symptomatic relief, and no additional metastatic lesions were detected, leading to a conservative follow‐up strategy. This case highlights the diagnostic utility of balloon‐assisted enteroscopy in detecting rare small bowel metastases. Given that such metastases often remain asymptomatic until reaching an advanced stage, early identification is critical. Furthermore, immunohistochemical profiling plays a crucial role in distinguishing metastatic endometrial cancer from other primary small bowel malignancies. Endoscopists should maintain a high index of suspicion for metastatic involvement in patients with a history of endometrial cancer who present with unexplained gastrointestinal symptoms.